Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1104/pp.18.01513
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Variations in Diurnal Growth Patterns and Metabolism Among Ulva spp. Strains

Abstract: Green macroalgae of the genus Ulva play a key role in coastal ecosystems and are of increasing commercial importance. However, physiological differences between strains and species have yet to be described in detail. Furthermore, the strains of Ulva used in aquaculture usually originate from opportunistic collection in the wild without prior selection of best performing strains. Hence, efforts are required to detect the potential variability in growth and metabolic accumulation between Ulva strains and ultimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 99 publications
(120 reference statements)
1
38
0
Order By: Relevance
“…Given the limited cytoplasmic genetic variation, we expect that the large growth and metabolic differences between Ulva individuals from the same species (Fort et al. 2019) is probably largely explained by variation in the nuclear genome. Our strategy did not allow for precise characterization of nuclear genome diversity due to limited coverage and high abundances of bacterial DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the limited cytoplasmic genetic variation, we expect that the large growth and metabolic differences between Ulva individuals from the same species (Fort et al. 2019) is probably largely explained by variation in the nuclear genome. Our strategy did not allow for precise characterization of nuclear genome diversity due to limited coverage and high abundances of bacterial DNA.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of genetic variation among foliose Ulva strains are associated with large differences in biomass production (Fort et al. 2019, 2020). Such genetic variation presents foliose Ulva as an attractive target for genomic improvement.…”
mentioning
confidence: 99%
“…Today, most of the land-based aquaculture operations of Ulva spp. is done by clonal propagation of multiple strains, normally collected in the vicinity of farming sites [15]. Species and/or strains selection of Ulva spp.…”
Section: Introductionmentioning
confidence: 99%
“…Although the favourable growth response to NH 4 + as the N source was shown in several studies, Fort et al (2019) recently reported that NO 3 − accumulation and consumption was positively correlated with Ulva spp. growth, with higher growth rates during the night than during light periods (Fort et al 2019). In the future, therefore, studies with a greater temporal resolution will be necessary to monitor the dynamics of N consumption in aquaculture.…”
Section: Fish-farming Water Increases the Nutrients Requiered In Macrmentioning
confidence: 93%
“…Ale et al (2011) reported a favourable growth response to NH 4 + relative to other N sources by monitoring the growth kinetics of U. lactuca (Ale et al 2011). Although the favourable growth response to NH 4 + as the N source was shown in several studies, Fort et al (2019) recently reported that NO 3 − accumulation and consumption was positively correlated with Ulva spp. growth, with higher growth rates during the night than during light periods (Fort et al 2019).…”
Section: Fish-farming Water Increases the Nutrients Requiered In Macrmentioning
confidence: 99%